THEORY AND PRACTICE OF ADAPTIVE TESTS USAGE - Smetanyuk Л.В.; Kravtsov Г.М. (Journal of Information Technologies in Education (ITE), 2009)
Results of tests modeling and adaptive testing process in the knowledge control system with use of adaptive tests in distance learning system «Kherson Virtual University» are presented.